Analysis of the Implementation of Musyarakah Financing Based on the Standard Book of Musyarakah Products at BPRS Baktimakmur Indah Branch Sepanjang - Badruzzaman; Fitri Nur Latifah (Indonesian Journal of Law and Economics Review, 2021)
The musyarakah financing product is a competitive flagship product of Bank Pembiayaan Rakyat Syariah (BPRS) which has not growth yet as like as other financing products. The lack of development of musyarakah financing products has caused BPRS to have more products based on fixed income financing which is similar to the conventional pattern that uses a fixed income structure. PT. BPRS Baktimakmur Indah is the largest BPRS It has assets Rp 163,147,899,000 and the financing provided has Rp 126,807,530 as of December 31, 2019. This research was conducted at BPRS Baktimakmur Indah Cabang Sepanjang Sidoarjo that located at Jln. Raya Bebekan No.21 Sepanjang kecamatan Taman, Kabupaten Sidoarjo. The purpose of this study was to analyze the implementation of musyarakah financing based on the standard book of musyarakah products published by Otoritas Jasa Keuangan (OJK). By using qualitative research methods through a phenomenological paradigm approach that requires researching a natural setting, with observation data collection techniques, direct interviews and literature from companies to support data needs. After the research was conducted, it was found that the BPRS Baktimakmur Indah Cabang Sepanjang had implemented musyarakah financing in accordance with the standard book of musyarakah products issued by Otoritas Jasa Keuangan (OJK).